Alegorična eksegeza Homerja, pripovedni suspenz in metapoezija v Vergilijevi pripovedi o Aristaju (Georg. IV 315-558) - Marinčič, Marko (Keria (Ljubljana), 2003)
The intertextual function of four Homeric passages which lie behind the finale of Vergil's Georgics (Il. 1 and 18, Od. 4 and 8) can be defined in terms of moralising exegesis in the line of Ecl. 2, Hor. Epist. 1,2, and with Plutarch, De aud. poet. 19f-20a as a later parallel. The Song of Clymene (Georg. 4,345-7), which has conventionally been linked with cosmological allegoresis of Homer, reelaborates the Homeric technique of foreshadowing; in the new generic context, however, this conventional technique of narrative poetry acquires a strong tendency towards philosophical didacticism.
Keywords: antična književnost; Homerus; literarna teorija; literarne študije; medbesedilnost; Plutarchus; poezija; Vergilius Maro, Publius